Konceptualizacja straty w cyklu wierszy Inny Lisnianskiej Без тебя - Nikadem-Malinowska, Ewa (Acta Polono-Ruthenica, 2018)
Inna Lisnianskaya’s cycle Без тебя consists of fourteen poems. It was written within four days - between 24 and 27 May 2003. Each poem presents the emotions felt by the lyrical subject who experiences a painful loss of a loved one. Lisnianskaya’s loss is conceptualised in a holistic manner - each poem constitutes an independent conceptualisation of loss, however, their hierarchy creates the superordinate concept the whole cycle is devoted to.